Download presentation

Presentation is loading. Please wait.

Published byPhoebe Dickerson Modified over 6 years ago

1
Exponential Equations

2
Do you remember how to solve 2 x = 16? 2 x = 16 An equation with unknown indices is called an exponential equation. 2 x = 2 4 x = 4 Example of an Exponential equation Express both sides as powers of 2

3
How to solve 2 2x + 2 x 6 = 0? Since 2 2x = (2 x ) 2, we can transform the original equation into a quadratic equation in 2 x.

4
Let me try to solve the equation. 2 2x + 2 x 6 = 0 (2 x ) 2 + 2 x 6 = 0 Let y = 2 x, the equation becomes y 2 + y 6 = 0 (y 2)(y + 3) = 0 y = 2 or y = 3 2 x = 2 or 2 x = 3 (rejected) 2 x = 2 1 x = 1 2 x is positive.

5
Follow-up question 2 2x + 4(2 x ) 32 = 0 Let y = 2 x, the equation becomes y 2 + 4y 32 = 0 (y 4)(y + 8) = 0 y = 4 or y = 8 2 x = 2 2 x = 2 2 x = 4 or 2 x = 8 (rejected) Solve 2 2x + 4(2 x ) 32 = 0. (2 x ) 2 + 4(2 x ) 32 = 0

6
How to solve the following simultaneous equations? By writing 81 = 3 4 and 4 = 2 2, the simultaneous exponential equations can be simplified. 3 x + y = 81 ……(1) 2 x + 5y = 4 ……(2)

7
Let me try to solve the equations. From (1), 3 x + y = 3 4 From (2), 2 x + 5y = 2 2 3 x + y = 81 ……(1) 2 x + 5y = 4 ……(2) x + y = 4 x + 5y = 2 x + y = 4 ……(3) x + 5y = 2 ……(4) The simultaneous equations become: Solving (3) and (4), we have

8
Follow-up question From (1), 2 x + 2y = 2 0 2 x + 2y = 1 ……(1) 5 x + 3y = ……(2) x + 2y = 0 ……(3) x + 3y = 1 ……(4) The simultaneous equations become: Solving (3) and (4), we have Solve the following simultaneous equations: x + 2y = 0 From (2), 5 x + 3y = 5 1 x + 3y = 1

Similar presentations

© 2022 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google